Konzeptionelle Erweiterungen im reflexiven Handeln im Modus des forschenden Lernens. Einblicke in die transformativen Lernprozesse am Beispiel des Seminars Unterrichtsforschung für DaF - Lazovic, Milica (2022)
This article analyses transformative processes, initiated through research-based learning, in the context of the seminar Classroom Research for Prospective Teachers of German as a Second Language. Starting from a theoretical insight into the relevance and dynamics of research-based learning, two aspects are ethnomethodologically focused on: self-awareness in the research-based learning process and transformative self-reflexivity on the one hand, and transformative processes, on the other, identified in student presentations and project work.
Keywords: second language teacher education; research-based learning; practical research